Integration of BIM and GIS Data of a Heritage Building Using FME - Borkowski, Andrzej Szymon; To Duc, Alex (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
BIM and GIS technologies are used in both planning and investment and construction processes. GIS is more often used in the former, where one operates on a macro scale and information about the environment is essential for decision-making. BIM, on the other hand, is increasingly implemented in investment and construction processes (micro scale). The BIM model as a resource of knowledge and information about the construction object is the basis for decision-making, while data from GIS systems are necessary to obtain reliable information about the environment and the prevailing spatial, social or economic conditions.
Keywords: BIM; GIS; FEM; 3D visualization; georeferencing; heritage; integration